How good are global DNA ‐based environmental surveys for detecting all protist diversity? Arcellinida as an example of biased representation - Fernando Useros; Iván García‐Cunchillos; Nicolas Henry; Cédric Berney; Enrique Lara (Environmental Microbiology, 2024)
Metabarcoding approaches targeting microeukaryotes have deeply changed our vision of protist environmental diversity. The public repository EukBank consists of 18S v4 metabarcodes from 12,672 samples worldwide. To estimate how far this database provides a reasonable overview of all eukaryotic diversity, we used Arcellinida (lobose testate amoebae) as a case study. We hypothesised that (1) this approach would allow the discovery of unexpected diversity, but also that (2) some groups would be underrepresented because of primer/sequencing biases. Most of the Arcellinida sequences appeared in freshwater and soil, but their abundance and diversity appeared underrepresented. Moreover, 84% of ASVs belonged to the suborder Phryganellina, a supposedly species‐poor clade, whereas the best‐documented suborder (Glutinoconcha, 600 described species) was only marginally represented. We explored some possible causes of these biases. Mismatches in the primer‐binding site seem to play a minor role. Excessive length of the target region could explain some of these biases, but not all. There must be some other unknown factors involved. Altogether, while metabarcoding based on ribosomal genes remains a good first approach to document microbial eukaryotic clades, alternative approaches based on other genes or sequencing techniques must be considered for an unbiased picture of the diversity of some groups.

Expansion of the cytochrome C oxidase subunit I database and description of four new lobose testate amoebae species (Amoebozoa; Arcellinida) - Giulia M. Ribeiro; Fernando Useros; Kenneth Dumack; Rubén González-Miguéns; Ferry Siemensma; Alfredo L. Porfírio-Sousa; Carmen Soler-Zamora; João Pedro Barbosa Alcino; Daniel J.G. Lahr; Enrique Lara (European Journal of Protistology, 2023)

RecruitNet : A global database of plant recruitment networks - Miguel Verdú; Jose L. Garrido; Julio M. Alcántara; Alicia Montesinos‐Navarro; Salomón Aguilar; Marcelo A. Aizen; Ali A. Al‐Namazi; Mohamed Alifriqui; David Allen; Kristina J. Anderson‐Teixeira; Cristina Armas; Jesús M. Bastida; et al. (Ecology, 2023)
Plant recruitment interactions (i.e., what recruits under what) shape the composition, diversity, and structure of plant communities. Despite the huge body of knowledge on the mechanisms underlying recruitment interactions among species, we still know little about the structure of the recruitment networks emerging in ecological communities. Modeling and analyzing the community‐level structure of plant recruitment interactions as a complex network can provide relevant information on ecological and evolutionary processes acting both at the species and ecosystem levels. We report a data set containing 143 plant recruitment networks in 23 countries across five continents, including temperate and tropical ecosystems. Each network identifies the species under which another species recruits. All networks report the number of recruits (i.e., individuals) per species. The data set includes >850,000 recruiting individuals involved in 118,411 paired interactions among 3318 vascular plant species across the globe. The cover of canopy species and open ground is also provided. Three sampling protocols were used: (1) The Recruitment Network (RN) protocol (106 networks) focuses on interactions among established plants (“canopy species”) and plants in their early stages of recruitment (“recruit species”). A series of plots was delimited within a locality, and all the individuals recruiting and their canopy species were identified; (2) The paired Canopy‐Open (pCO) protocol (26 networks) consists in locating a potential canopy plant and identifying recruiting individuals under the canopy and in a nearby open space of the same area; (3) The Georeferenced plot (GP) protocol (11 networks) consists in using information from georeferenced individual plants in large plots to infer canopy‐recruit interactions. Some networks incorporate data for both herbs and woody species, whereas others focus exclusively on woody species. The location of each study site, geographical coordinates, country, locality, responsible author, sampling dates, sampling method, and life habits of both canopy and recruit species are provided. This database will allow researchers to test ecological, biogeographical, and evolutionary hypotheses related to plant recruitment interactions. There are no copyright restrictions on the data set; please cite this data paper when using these data in publications.

Cyphoderia ampulla (Cyphoderiidae: Rhizaria), a tale of freshwater sailors: The causes and consequences of ecological transitions through the salinity barrier in a family of benthic protists - Rubén González‐Miguéns; Carmen Soler‐Zamora; Fernando Useros; Sandra Nogal‐Prata; Cédric Berney; Andrés Blanco‐Rotea; María Isabel Carrasco‐Braganza; David de Salvador‐Velasco; Antonio Guillén‐Oterino; Daniel Tenorio‐Rodríguez; David Velázquez; Thierry J. Heger; et al. (Molecular Ecology, 2022)
The salinity barrier that separates marine and freshwater biomes is probably the most important division in biodiversity on Earth. Those organisms that successfully performed this transition had access to new ecosystems while undergoing changes in selective pressure, which often led to major shifts in diversification rates. While these transitions have been extensively investigated in animals, the tempo, mode, and outcome of crossing the salinity barrier have been scarcely studied in other eukaryotes. Here, we reconstructed the evolutionary history of the species complex Cyphoderia ampulla (Euglyphida: Cercozoa: Rhizaria) based on DNA sequences from the nuclear SSU rRNA gene and the mitochondrial cytochrome oxidase subunit I gene, obtained from publicly available environmental DNA data (GeneBank, EukBank) and isolated organisms. A tree calibrated with euglyphid fossils showed that four independent transitions towards freshwater systems occurred from the mid‐Miocene onwards, coincident with important fluctuations in sea level. Ancestral trait reconstructions indicated that the whole family Cyphoderiidae had a marine origin and suggest that ancestors of the freshwater forms were euryhaline and lived in environments with fluctuating salinity. Diversification rates did not show any obvious increase concomitant with ecological transitions, but morphometric analyses indicated that species increased in size and homogenized their morphology after colonizing the new environments. This suggests adaptation to changes in selective pressure exerted by life in freshwater sediments.